Penyuluhan Pendidikan Seksual di SMKN 1 Jakarta - Kusuma, Aliyah Mu'Adzah; Wahyuningtyas, Widayani; Andini, Sarah Sabina; Anam, Ahmad Khoirul; Rachenda, Zahwa Maulida; Khotaman, Rihana Salsabila (Abdimas Indonesian Journal, 2024)
Adolescence, as an important period of transition from childhood to adulthood, is often marked by a lack of sexual education. Lack of sexual education causes many problems related to sexual deviation and sexual harassment to occur in adolescence. To reduce this problem in teenagers, this community service is carried out to provide knowledge in overcoming the problem of lack of knowledge regarding sexual education. The implemented method involves conducting a seminar at SMK Negeri 1 Jakarta on October 30, 2023, specifically for students of class XI DPIB 1. Data collection is carried out through the completion of a questionnaire comprising eight multiple-choice questions and two essay questions. The preparation stage for the seminar involves the development of content, titles, questions, games, pre and post-test questionnaire links, and prize determination. The presentation of material encompasses aspects of sexual health, sexually transmitted diseases, reproductive organ care, catcalling, and sexual harassment. The question and answer session allows active participation of respondents, facilitating in-depth discussions about their views on these issues. The use of the questionnaire as the primary instrument ensures understanding of key aspects, with a scoring of 10 points for each correct answer to multiple-choice questions. This community service demonstrates the necessity of comprehensive sexual education for adolescents to address reproductive and sexual health issues. Through a positive and interactive approach, it is expected that adolescents can make responsible decisions and possess adequate knowledge regarding their sexual changes. By involving schools and teachers as facilitators, this community service seeks to provide a platform for a better understanding of this sensitive topic in an effort to prevent various negative impacts that may arise due to a lack of sexual education.